2001
DOI: 10.1093/emboj/20.16.4380
|View full text |Cite
|
Sign up to set email alerts
|

The PIF-binding pocket in PDK1 is essential for activation of S6K and SGK, but not PKB

Abstract: PKB/Akt, S6K1 and SGK are related protein kinases activated in a PI 3-kinase-dependent manner in response to insulin/growth factors signalling. Activation entails phosphorylation of these kinases at two residues, the T-loop and the hydrophobic motif. PDK1 activates S6K, SGK and PKB isoforms by phosphorylating these kinases at their T-loop. We demonstrate that a pocket in the kinase domain of PDK1, termed the`PIF-binding pocket', plays a key role in mediating the interaction and phosphorylation of S6K1 and SGK1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
376
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 336 publications
(388 citation statements)
references
References 36 publications
12
376
0
Order By: Relevance
“…3B, 5A, and 6C). Biondi and colleagues (27) have demonstrated that, in vitro, a carboxyl-terminally truncated S6K1 is a much better PDK1 substrate when the S6K1 H-motif is changed to a phosphomimic glutamate. Furthermore, PDK1 interacts with this Thr3 Glu mutant more efficiently.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3B, 5A, and 6C). Biondi and colleagues (27) have demonstrated that, in vitro, a carboxyl-terminally truncated S6K1 is a much better PDK1 substrate when the S6K1 H-motif is changed to a phosphomimic glutamate. Furthermore, PDK1 interacts with this Thr3 Glu mutant more efficiently.…”
Section: Discussionmentioning
confidence: 99%
“…A phosphopeptide modeled after the phosphorylated H-motif of S6K1 binds much more efficiently to PDK1 than the unphosphorylated peptide (26), potentially explaining the strongly synergistic nature of H-motif and T-loop phosphorylation of S6K1. Moreover, when coexpressed in cells, PDK1 binds much more efficiently to an S6K1 variant bearing a phosphomimic H-motif substitution (27), suggesting that the phosphorylated H-motif provides a surface with which PDK1 makes physical contact. Akt is also phosphorylated and activated by PDK1.…”
mentioning
confidence: 99%
“…To confirm the role of PDK1-Akt/mTOR pathway in liver regeneration, we employed the "pif-pocket" mutant of PDK1, which allows PDK1 to signal exclusively to Akt but not to p70 S6K or others. 30,[34][35][36] Adenovirus-mediated introduction of the pif-pocket mutant (L155E) did re-phosphorylate Akt (Thr308), but not p70 S6K (Thr389), 4 hours after PH in L-Pdk1KO mice (Fig. 5A).…”
Section: L-pdk1komentioning
confidence: 96%
“…This form of regulation by compartmentation is disrupted by expression of constitutively active Sgk1 isoforms, which results in indiscriminate activation of all pathways. Subsequent phosphorylation of the activation loop of Sgk1 by PDK1 (T253) is not restricted by compartmentalization because, as elegantly demonstrated by Alessi's group (Biondi et al, 2001), this phosphorylation event is independent of phosphatidylinositol-3-phosphate and follows a mechanism different from the one used in the phosphorylation of the equivalent residue of Akt.…”
Section: Functional Implications Of Sgk1 Isoformsmentioning
confidence: 97%